2022
DOI: 10.3389/fenvs.2021.749864
|View full text |Cite
|
Sign up to set email alerts
|

Purposeful Stakeholder Engagement for Improved Environmental Flow Outcomes

Abstract: Rivers are dynamic social-ecological systems that support societies and ecosystems in a multitude of ways, giving rise to a variety of user groups and competing interests. Environmental flows (e-flows) programs developed to protect riverine environments are often conceived by water managers and researchers. This is despite continued calls for increased public participation to include local communities and Indigenous peoples in the development process. Failure to do so undermines social legitimacy and program e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 143 publications
0
6
0
Order By: Relevance
“…Jackson (2015) called for water decision-makers to alter their current approach so as to avoid utilitarian values trumping relational ones. Therefore, many of the legitimacy issues surrounding environmental water stem from programme objectives and the methods used to address these objectives, including expert opinions that do not reflect community values (Kosovac 2022, Mussehl et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jackson (2015) called for water decision-makers to alter their current approach so as to avoid utilitarian values trumping relational ones. Therefore, many of the legitimacy issues surrounding environmental water stem from programme objectives and the methods used to address these objectives, including expert opinions that do not reflect community values (Kosovac 2022, Mussehl et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Since its emergence from the physical sciences, environmental water management has seen an expansion in interdisciplinary approaches over the last 20 years (Horne et al 2017b, Poff et al 2017). There has been a growing recognition of the importance of participatory processes for water planning and management (Conallin et al 2017, Mussehl et al 2022), including perspectives from local communities as well as Indigenous peoples (Pahl-Wostl et al 2013, Robinson et al 2018, Anderson et al 2019). Similarly, there is also a growing awareness that the legitimacy of water allocation and planning stems from both the outcomes achieved (healthy river systems) and the processes used (in which all members of the affected community have had an opportunity to be heard; O’Donnell et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Eaton, Brasier [72] developed a conceptual framework which acts as a guide to understanding the effects of stakeholder engagement on environmental, social, and behavioural change. However, regardless of the approach used, stakeholder engagement must be integrated into an adaptive management system for managing risks and uncertainties [60,73].…”
Section: Stakeholder Engagementmentioning
confidence: 99%
“…It has been applied in many settings, particularly involving marginalized groups in areas such as health care and resource management (Baum et al, 2006;Grilli et al, 2021). In Australia, it is increasingly being employed to facilitate active involvement of Traditional Owners in areas of land management (Walter, 2009;Mussehl et al, 2022).…”
Section: Water Justice and Participatory Action Researchmentioning
confidence: 99%
“…The rise in water-based citizen science programs has demonstrated that communities are concerned about their waterways and interested to enhance their knowledge through scientific practice. However, there have been challenges in the utilization of this data by management authorities, often to the disappointment of the volunteer participants (Mussehl et al, 2022). In addition, there are multiple ways to demonstrate care and knowledge of place, through story, journaling, and other arts-based practice.…”
Section: Introductionmentioning
confidence: 99%